Motivations of beer purchase among Singapore undergraduates. - Ng, Roy Choon. (2011)
This study examines the relationship between brand perception, taste, peer influence and beer purchase. The moderating effect of marketing communication tools on the relationship between brand perception and beer purchase, with relation to undergraduates, was also investigated. A total of 7 hypotheses were developed and evaluated based on data collected via self-administered surveys through judgment sampling. Our findings have ascertained the positively significant relationship between brand perception, taste, peer influence and beer purchase, that has been previously derived by other researchers. The general stereotype of men drinking more than women was also justified. However, in contrast to previous findings, all marketing communication tools were found to have a negative moderating effect on the brand perception-beer purchase relationship, with the sole exception of social media, having a positive but insignificant effect. More notably, our findings indicated a mediating effect of brand perception on taste, peer influence and beer purchase, of which, a closed-loop relationship was ascertained between brand perception and peer influence. These findings suggest that marketers should consider implementing Word-of-Mouth advertising through social media. A total of 271 undergraduates took part in the study.